Storytelling that Sells: Building Strong and Memorable Brands Through Narrative (Management Studies and Business Journal (PRODUCTIVITY), 2024)
The integration of the concept of "Brand Stories" in marketing with data-based marketing strategies has become the focus of attention in efforts to improve business performance and consumer engagement. This article presents the results of a systematic literature review aimed at exploring the potential and impact of this integration. By analyzing related studies from the period 2019 to 2024, we conclude that the integration of brand storytelling and data-driven marketing has great potential in improving sales results and consumer engagement. The practical implications of these findings are presented to provide guidance for marketing practitioners in designing more effective marketing strategies.